Auditory perceptual learning is not affected by anticipatory anxiety in the healthy population except for highly anxious individuals: EEG evidence. Issue 7 (July 2019) - Fucci, E.; Abdoun, O.; Lutz, A.
Highlights: Anxious hypervigilance sensitizes early brain responses to unrelated stimuli. Perceptual learning is affected only in individuals with high state or trait anxiety. Differences in the modulation of neural processes confirm anxiety as a dimensional construct. Abstract: Objective: A recent neurocomputational model proposed that anxious hypervigilance impedes perceptual learning. This view is supported by the observed modulation of the mismatch negativity (MMN), a biomarker of implicit perceptual learning processes, in anxiety disorders. However, other studies found that anxious states sensitize brain responses with no impact on perceptual learning. The present research aimed to elucidate the impact of anticipatory anxiety on early stimulus processing in the healthy population. Methods: We used electroencephalography to investigate the impact of unpredictable threat on the amplitude of the MMN and other components of the auditory evoked response in healthy participants during a passive auditory oddball task. Results: We found a general sensitization of early components of the auditory evoked response and changes in subjective and autonomic measures of anxiety during threat periods. The MMN amplitude did not differ during threat, compared to safe periods. However, this difference was modulated by the level of state or trait anxiety. Conclusion: We propose that anxiety sensitizes early brain responses to unspecific environmental stimuli but affects implicit perceptual learning processes only when an individual is located at the higher end of the anxiety spectrum. Significance: This view might distinguish between an adaptive role of anxiety on processing efficiency and its detrimental impact on implicit perceptual learning observed in psychiatric conditions.